Effects of Guided Inquiry and Task Hierarchy Analysis Model in Cooperative Learning Strategy on Chemistry Students’ Performance in Imo State - Nwafor Chimuanya Leonard; A. U Nwanekezi (European Scientific Journal, ESJ, 2018)
The study investigated the effects of guided inquiry and task hierarchy analysis model in cooperative learning strategy on Chemistry students’ performance in Nwangele Local Government Area, Imo State. The study adopted Pretest Posttest non-equivalent quasi-experimental design. One hundred and sixty-three Chemistry students from six public schools purposively selected participated in the study. Chemistry Performance Test on Acid-Base Reactions (CPTABR) which also tested retention with a reliability index of 0.75 was developed, validated and used for data collection. Research questions were answered using mean and Standard deviation, while the null hypotheses were tested using Analysis of Covariance at 0.05 significance level. The result revealed that Guided Inquiry Learning Strategy (GILS) and Task Hierarchy Analysis Model (THAM) in Cooperative Learning Strategy (CLS) proved to be more effective than lecture method (LM) in understanding of Acid-Base Reactions. It was recommended that Guided Inquiry Learning Strategy (GILS) and Task Hierarchy Analysis Model (THAM) in Cooperative Learning Strategy (CLS) should be used by Chemistry teachers to teach Acid- Base Reactions to enhance students’ performance and retention in Chemistry.